Application of SmartPLS in Analyzing Critical Success Factors for Implementing Knowledge Management in the Education Sector - Jacqueline, Greisy; Putri Ayu Senjaya, Yulia; Firli, M.Zaki; Bayu Yadila, Ahmad (Pandawan, 2024)
This research explores the critical success factors influencing the implementation of knowledge management in the education sector, employing Structural Equation Modeling (SEM) with SmartPLS as the analytical tool. The study addresses the intricate challenges inherent in knowledge management within educational environments, aiming to provide a nuanced understanding of the factors contributing to successful implementation The conceptual framework identifies key factors, including HRM-Driven Knowledge Sharing, IT Integration in Teaching Practices, Organizational Culture Alignment, Perceived Effectiveness of Teacher Training, and Perceived Top Management Support. The chosen methodology, utilizing SmartPLS, is justified for its suitability in handling challenges associated with small sample sizes and non-normal data distributions. The data analysis reveals the generally robust reliability of constructs but also underscores potential concerns related to discriminant validity among certain variables. The research contributes significantly to the understanding of critical success factors for knowledge management in education. However, the conclusion suggests the need for refinement in the conceptual model to enhance the validity and applicability of the findings. In conclusion, this research offers a comprehensive perspective on the complexities of implementing knowledge management in the education sector. The findings pave the way for potential enhancements to the conceptual model, aiming to elevate the effectiveness of knowledge management practices within educational contexts.